Exploring The Use Of Knowledge-Based View In Accounting And The Business Environment - Zul Azmi; Erlina Erlina; Iskandar Muda; Keulana Erwin (UNIVED Press, 2024)
This paper aims to explore the benefits of a knowledge-based view in accounting practices and the business environment. The goal is to explain why the knowledge-based view can provide insight into the importance of knowledge management in the business environment. By using a literature review approach, we try to study previous research related to knowledge-based view theory in accounting practices and the business environment. The results show that KBV has proven its value in accounting practice by providing a better understanding of how organizational knowledge and expertise can be a source of competitive advantage, and lead to innovation in organizations more widely. This study contributes to the literature to explain why the usefulness of the knowledge-based view is important for explaining organizational innovation including in accounting practices and the business environment.